Consumer Sentiment and Economic Activity A Cross Country Comparison - Golinelli, Roberto (OECD Publishing, 2004)
The objective of this article is to reassess the validity of the consumer confidence (or sentiment) indices in anticipating the evolution of economic activity by considering a fairly high number of countries across the world (i.e. France, Germany, Italy, UK, USA, Japan, Canada and Australia) over a period of about thirty years, from the beginning of the seventies till the end of 2002 (quarterly data). To our knowledge this is the first attempt to analyse the consumer confidence index for several countries over such a long period of time. We model the CSIoutput relationship in a cointegrated vector autoregression (VAR) framework, by considering a common set of variables for all countries. Our findings suggest that: (a) what appears to be the main driving forces of consumer confidence cannot be simply summarised on the basis of ...